2020
DOI: 10.3892/mmr.2020.10911
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of formononetin on the monocrotaline‑induced pulmonary arterial hypertension in rats

Abstract: Pulmonary arterial hypertension (PaH) is a fatal syndrome resulting from enhanced pulmonary arterial pressure and pulmonary vessel resistance. Perivascular inflammation and extracellular matrix deposition are considered to be the crucial pathophysiologic bases of PaH. Formononetin (FMn), a natural phytoestrogen isolated from red clover (Trifolium pratense), has a variety of proapoptotic, anti-inflammatory and anti-tumor activities. However, the therapeutic effectiveness of FMn for PaH remains unclear. in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Pulmonary arterial hypertension is also a common but devastating cardiovascular disease based on VR ( Thompson and Lawrie, 2017 ). In the present study, we used the previously described method to establish a pulmonary arterial hypertension model ( Wu et al, 2020 ) and observed that the rats, which received daily SSE treatments two weeks subsequent to the MCT injection, had large decreases in right ventricular hypertrophy, pulmonary arterial remodeling, and pulmonary artery pressure compared with only MCT injected rats. Collectively, these results show the suppressive effect of SSE on VR-related diseases.…”
Section: Discussionmentioning
confidence: 85%
“…Pulmonary arterial hypertension is also a common but devastating cardiovascular disease based on VR ( Thompson and Lawrie, 2017 ). In the present study, we used the previously described method to establish a pulmonary arterial hypertension model ( Wu et al, 2020 ) and observed that the rats, which received daily SSE treatments two weeks subsequent to the MCT injection, had large decreases in right ventricular hypertrophy, pulmonary arterial remodeling, and pulmonary artery pressure compared with only MCT injected rats. Collectively, these results show the suppressive effect of SSE on VR-related diseases.…”
Section: Discussionmentioning
confidence: 85%
“…Collectively, both in vivo and in vitro studies demonstrate that naringin is able to delay the development of PAH through the inhibition of EndMT. ERK and NF-κB signalling pathways have been reported as important factors in the maintenance of pulmonary vascular homeostasis (Cai et al, 2019;Wu et al, 2020). Increasing evidences have demonstrated the associations of ERK and NF-κB signalling pathways in the EndMT in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricle systolic pressure (RVSP) measurement was conducted as in a previous study (Wu et al, 2020). Briefly, pentobarbital sodium (60 mg/kg, Sigma-Aldrich, MO, United States) through intraperitoneal (i.p.)…”
Section: Hemodynamic Measurementmentioning
confidence: 99%
“…For example, studies showed that FMNT decreased the level of p-NF-κB p65 and increased the level of IκBα, the inhibitor of NF-κB, in the liver from concanavalin-A-induced autoimmune hepatitis mice, showing a powerful immunomodulatory property . FMNT also possess activity of restraining monocrotalinetreated pulmonary arterial hypertension, whose pharmacological mechanism was related to the downregulation of phosphorylated ERK and NF-κB (Wu et al, 2020). In addition to the inflammation model mentioned above, NF-κB pathway plays a critical role in mastitis.…”
Section: Nf-κb Pathway Inhibitionmentioning
confidence: 99%